Analisis Peran Internasinal Networking For Humanitarian (INH) dalam Membantu Warga Gaza Palestina di Tengah Konflik - Shofa, Ahmad Ainus Shofa; Nilam, Yulita (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2025)
This research aims to analyze INH's role in helping the Palestinian people, with a focus on the programs implemented and the challenges faced in distributing aid. By using a qualitative approach and analysis of secondary data from various sources, this research is expected to provide in-depth insight into INH's contribution in the context of the humanitarian crisis in Gaza and the impact of the conflict on Palestinian civilians. The research results show that although INH has succeeded in distributing significant aid, logistical challenges and the security situation remain the main obstacles in their efforts to provide well-targeted aid. This research also underscores the importance of continued international support to strengthen humanitarian efforts in these conflict areas.